Identifikasi Senyawa Natrium Benzoat pada Cabai Merah Giling yang Dijual di Pasar Raya Kota Padang - Zakiya Zar'a; Elmatris Elmatris; Laila Isrona (Fakultas Kedokteran, Universitas Andalas, 2020)
Background. Red chili is a spice that is consumed by many people, in the form of fruit or grinded. Grinded red chili has a low shelf life and is easily overgrown by destructive microorganisms, therefore it needs preservatives such as sodium benzoate which can inhibit the destruction. Based on regulation of National Agency of Drug and Food Control Republic of Indonesia No. 36/2013, the maximum limit of sodium benzoate in seasoning is 0.6 g/kg. Objective. to identify sodium benzoate and its level in grinded red chili has been sold in Pasar Raya Padang based on BPOM standard. Methods. The type of research is descriptive research, conducted at UPTD Balai Laboratorium Kesehatan Sumatera Barat from September 2019 to July 2020. The research sample consisted of 35 samples obtained by total sampling method. Results. All of grinded red chilies used as sample were positive containing sodium benzoate. Average levels of sodium benzoate in grinded red chili is 0,144 g/kg. The level of sodium benzoate in each sample is below National Agency of Drug and Food Control Republic of Indonesia standard (<0,6 g/kg). Conclusion. All samples of grinded red chilies were positive containing sodium benzoate with appropriate levels as stated in National Agency of Drug and Food Control Republic of Indonesia provision. Keywords : grinded red chili, sodium benzoate, Spectrophotometer UV-Visible.